Logic programming and nonmonotonic reasoning : 14th International Conference, LPNMR 2017, Espoo, Finland, July 3-6, 2017, Proceedings /: 14th International Conference, LPNMR 2017, Espoo, Finland, July 3-6, 2017, Proceedings. (2017) - Unknown
No abstract available